Nasal intubation with bronchial blocker in a patient with difficult airway for thoracoscopic surgery - Koli, Deepak C.; Kadakia, Aditi P.; Latkar, Prajakta D.; Mehta, Hemant H. (International Journal of Research in Medical Sciences, 2021)
We describe a case report of a 49 years old male, a case of Carcinoma tongue with one finger mouth opening operated multiple times, currently presented with pleural based soft tissue lesion in lower lobe of left lung with query metastasis posted for video assisted thoracoscopy surgery (VATS) SOS open thoracotomy and wedge resection of the lesion. Considering difficult airway due to restricted mouth opening we opted for an awake nasal fiberoptic intubation followed by general anaesthesia. One lung ventilation was achieved with CoopdechTM bronchial blocker type A with standard cuff size in left main stem bronchus. Postoperative course of patient was uneventful. In this case report we highlight the importance of use of fiberoptic bronchoscope and bronchial blocker for lung deflation in the management of difficult airway in VATS, as incomplete deflation of the nondependent lung during VATS can lead to poor surgical exposure and inadequate space for surgical manipulation which in turn can compromise the success of the procedure, and may possibly lead to conversion into an open approach.